JSTL practical guide for JSP programmers - Spielman, Sue. (Amsterdam ; Boston : Elsevier/Morgan Kaufmann, 2004)
Web developers and page authors who use JavaServer Pages (JSP) know that it is much easier and efficient to implement web pages without reinventing the wheel each time. In order to shave valuable time from their development schedules, those who work with JSP have created, debugged, and used custom tagsa set of programmable actions that provide dynamic behavior to static pagespaving the way towards a more common, standard approach to using Java technology for web development. The biggest boost to this effort however has only recently arrived in the form of a standard set of tag libraries, known as the JSTL, which now provides a wide range of functionality and gives web page authors a much more simplified approach to implementing dynamic, Java-based web sites. JSTL: Practical Guide for JSP Programmers is a timely resource for anyone interested in doing large-scale J2EE application development. It sticks to the main features of the JSTL so that developers don't have to sift through unnecessary details to begin using the tags and working with the expression language. Sue Spielman's straight-forward, practical approach is enhanced with numerous code samples and insightful descriptions to make learning the JSTL a quickly and easily accomplished task. * Written by a best-selling author with a wealth of development experience and recognition in the Java community. * Covers the core elements of the JSTL including the four standard tag libraries (core, internationalization/format, XML, and SQL) and expression language. * Includes a reference section for all of the tabs and attributes contained in the JSTL. * Via a companion web site, provides downloadable code for the code samples in the book.
JSTL basics -- Using the expression language -- Working with the core actions -- Working with the XML actions -- Working with the internationalization and formatting actions -- SQL tag library using the SQL actions -- JSTL quick reference.
Includes index.
Keywords: Java (Computer program language).; JavaServer pages; Electronic books